2012
DOI: 10.1371/journal.pntd.0001833
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania Metacyclogenesis Is Promoted in the Absence of Purines

Abstract: Leishmania parasites, the causative agent of leishmaniasis, are transmitted through the bite of an infected sand fly. Leishmania parasites present two basic forms known as promastigote and amastigote which, respectively, parasitizes the vector and the mammalian hosts. Infection of the vertebrate host is dependent on the development, in the vector, of metacyclic promastigotes, however, little is known about the factors that trigger metacyclogenesis in Leishmania parasites. It has been generally stated that “str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 42 publications
0
58
0
1
Order By: Relevance
“…For instance, iron acquisition is important for Leishmania species growth and differentiation in vitro , involving the coupled activities of a membrane-associated ferric reductase ( LFR1 ) and a ferrous iron transporter ( LIT1 ) (3236). Another example is adenosine, which activates the ABC transporter systems that in turn suppress Leishmania species metacyclogenesis (37). We hypothesize that local bacterial genera in the vector provide the signals that trigger parasite differentiation either directly, by altering the concentration of key nutrients that trigger parasite differentiation, or indirectly, through effects on sand fly epithelial cell biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, iron acquisition is important for Leishmania species growth and differentiation in vitro , involving the coupled activities of a membrane-associated ferric reductase ( LFR1 ) and a ferrous iron transporter ( LIT1 ) (3236). Another example is adenosine, which activates the ABC transporter systems that in turn suppress Leishmania species metacyclogenesis (37). We hypothesize that local bacterial genera in the vector provide the signals that trigger parasite differentiation either directly, by altering the concentration of key nutrients that trigger parasite differentiation, or indirectly, through effects on sand fly epithelial cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Exemplified by the fact that adenosine deprivation stimulates metacyclogenesis (37), the local nutrient concentration may provide the necessary signals for Leishmania differentiation. Our data clearly indicate that specific microbial content is vital for L. infantum parasites to survive and successfully differentiate to an infective stage in the sand fly midgut, although the bacterium-associated biochemical mechanisms that trigger Leishmania replication and metacyclogenesis remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this particular type of nutrient stress may be an important regulator of parasite infectivity. Adenosine supplementation negatively impacts the efficiency of in vivo metacyclogenesis, the process wherein poorly infective procyclic promastigotes in the sandfly midgut differentiate into highly infective metacyclic promastigotes, primed for survival within a vertebrate host (8). A robust and reproducible purine stress response is easily induced in vitro by omission of purines from the growth medium, and we showed that purine-starved Leishmania donovani promastigotes enter a reversible quiescent-like state in which they can persist for over three months (14,16,17).…”
mentioning
confidence: 87%
“…As these compartments differ substantially in pH, temperature, and nutrient availability, Leishmania must undergo dramatic metabolic and physiological transformations to adapt to life in their respective hosts (2,3). Such environmental responses are so intertwined with the leishmanial lifecycle that several stressors function as cues for parasite differentiation, triggering the transition from one developmental stage to the next (4)(5)(6)(7)(8). Despite their importance to parasite biology, relatively little is known of the molecular mechanisms that allow Leishmania to respond to fluctuations in the extracellular milieu.…”
mentioning
confidence: 99%
“…Mediante pruebas inmunohistoquímicas se demostró que el LPG en las formas promastigotes procíclicas y metacíclicas que se encuentran adheridas al epitelio del intestino medio del vector, cuentan con residuos de β(1,3)glucosa; otras modificaciones que han sido involucradas en esta interacción del parásito con el vector son la galactosa, la manosa y la glucosa (19,20) . La transformación de promastigotes procíclicos a metacíclicos involucra modificaciones bioquímicas, moleculares y genéticas que proporcionan al promastigote metacíclico resistencia a la lisis mediada por el complemento (21,22) , facilitan el proceso de fagocitosis por los macrófagos (22) , aseguran la supervivencia del parásito en condiciones adversas en el fagolisosoma del macrófago, inducen la formación de proteínas de la familia de las quinasas y regulan la producción del óxido nítrico en las vacuolas fagocitóforas (20,23) .…”
Section: Introductionunclassified